An Analysis of Supplementary Reading Material Based on Students’ Preference - Vavia Darmayanti; Syahrial Syahrial; Wisma Yunita (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
The aims of this study were to find out the types of text of supplementary reading material chosen by students based on their preference and to investigate the students’ reasons in choosing the types of text of supplementary reading material at grade VIII of SMPN 1 Kepahiang. This research was categorized as descriptive quantitative and qualitative research. The subjects were the students of grade VIII who are chosen by using semi random sampling. The data was collected by using text types list and open ended questions. The researcher asked the students to choose types of text which were prefered by them, from total 50 texts the students must choose twenty texts. Then, to know the reason why they chose those texts, the researcher did an open ended questions to 20 students randomly. There were two findings of this research; (1) the type of text for supplementary reading material chosen by mostly students based on their preference at grade VIII of SMPN 1 Kepahiang was narrative text; (2) there were three students’ reasons in choosing the types of text for supplementary reading material at grade VIII of SMPN 1 Kepahiang, they were; the narrative text contains some stories which can entertain them, the narrative text is interesting to read, and the narrative text is easy to understand. Due to the limited sample taken in this research and the situation on Covid-19, it was suggested for further researcher to conduct similar research in more numbers of sample by conducting research in the classroom directly.